ONE- BOAT MID WATER TRAWLING WITH UNEQUEL PANELLED TRAWL - MHALATHKAR, H N; VIJAYAN, V; MATHAI, T JOSEPH; GEORGE, T P (Fishery Technology, 2017)
Results of the comparative efficiency studies with 10.5 m equal panelled and 10.3 m unequal panelled midwater trawls operated from 10.9 m wooden trawler are presented. Out of the two nets, the latter proved to be relatively good for the capture of off bottom and column fishes like pomfrets, seer, lactarius, cat fish, silver bar, ribbon fish and an increase of 84.4% in total catch was observed.